The Impact of the Introduction of the Additional Roles Reimbursement Scheme on the General Practice Nursing Workforce in England - Alison Leary; Geoffrey Punshon; Angie Hack; Dave Bushe; Crystal Oldman (Journal of Primary Care & Community Health)
Introduction/Objectives: To understand the impact of introducing Additional Roles Reimbursement Scheme (ARRS) on the General Practice Nurse (GPN) workforce. A workforce/people impact assessment designed as a cross-sectional survey of a stratified sample of 900 GPN on the Queen’s Nursing Institute mailing list. Method: A workforce/people impact assessment was designed based on the UKCS 2014 piloted and distributed as a cross-sectional survey via a survey platform. This included questions on level of impact, kind of impact and perception of prior engagement. Data were analyzed using descriptive statistics and content analysis. Results: The survey consisted of 21 questions (531 responses, response rate of 60%). ARRS deployment appears to have impacted the GPN workforce in several ways. There was positive impact on workloads from ARRS roles working in original scope, for example pharmacists medicine reviews. However, any benefit was offset by the increased workloads created by those new to general practice and/or working outside of traditional scope. This ranged from a lack of resources to provide the support those new to primary care require to practice safely, the expectations of others-that GPN will fill the gap in support and teaching to GPN directly safety netting the work of others. There was a lack of consultation regarding a major workforce change, leading to feelings of devaluation. There are some significant equity issues highlighted particularly around pay and opportunity. Conclusion: The introduction of ARRS has had some positive but mostly negative impact on the workload and introduced pay inequity issues on GPN.